English for international tourism : - Strutt, Peter (Pearson Education Limited, 2003)
English for International Tourism is the first multi-level series designed specifically for the hotel and tourism industry! This course focuses on the grammar, vocabulary, and skills needed for professional communication in this fast-paced industry.